Parental Perspectives on Their Grade 4 Children with Reading and Writing Difficulties in Mainstream Government Schools in Mauritius - Veerabudren, Sattiavany; Kritzinger, Alta; Graham, Marien; Roux, Mia le; Geertsema, Salomé (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2021)
Reading and writing difficulties (RWD) in learners pose significant challenges not just for children but also for parents. While there is limited support available for children with RWD and their parents in Mauritian schools, research may reveal areas of parental need that speech-language therapists may address. The aim was to determine parents’ perspectives regarding their Grade 4 children with RWD in mainstream government schools in Mauritius. Teachers identified children with RWD with the Screening Tool for Learning Disorder, and parents were requested to participate in the study. Sixty-seven parents completed a questionnaire investigating their perspectives on the symptoms and causes of their child’s RWD and the ways in which they assist their child. The screening tool differentiated between children at risk of specific learning disorder (SLD) and children who indicated clear symptoms of SLD. The results of the tool did not correspond closely with the participants’ satisfaction with their child’s academic performance. The majority of participants could, however, identify RWD in their children when descriptions were given. Parents mostly cited laziness as the main cause of their child’s RWD. The results showed that participants had limited information about the causes and symptoms of RWD and SLD. There is a lack of awareness about the role of speech-language therapists in the intervention of RWD. There are limited resources and support for children with RWD, despite an inclusive education policy in Mauritius. Speech-language therapists and teachers should collaborate to support children with RWD and their parents using inclusive education strategies.